Regularity of Viscous Solutions for a Degenerate Non-linear Cauchy Problem (Journal of Partial Differential Equations, 2016)
" We consider the Cauchy problem for a class of nonlinear degenerate parabolic equation with forcing. By using the vanishing viscosity method it is possible to construct a generalized solution. Moreover, this solution is a Lipschitz function on the spatial variable and H\u00f6lder continuous with exponent 1\/2 on the temporal variable."
Keywords: Viscosity solution; Hölder estimates; Hölder continuity